2016
DOI: 10.1073/pnas.1524636113
|View full text |Cite
|
Sign up to set email alerts
|

Calcium sensor regulation of the Ca V 2.1 Ca 2+ channel contributes to short-term synaptic plasticity in hippocampal neurons

Abstract: Short-term synaptic plasticity is induced by calcium (Ca 2+ ) accumulating in presynaptic nerve terminals during repetitive action potentials. Regulation of voltage-gated Ca V 2.1 Ca 2+ channels by Ca 2+ sensor proteins induces facilitation of Ca 2+ currents and synaptic facilitation in cultured neurons expressing exogenous Ca V 2.1 channels. However, it is unknown whether this mechanism contributes to facilitation in native synapses. We introduced the IM-AA mutation into the IQ-like motif (IM) of the Ca … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
44
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(49 citation statements)
references
References 41 publications
5
44
0
Order By: Relevance
“…Our previous studies of IM-AA mice showed that regulation of presynaptic Ca V 2.1 channels by CaS proteins contributes substantially to short-term synaptic plasticity in hippocampal synapses (21). In those studies, we found that the IM-AA mutation does not alter the frequency or amplitude of miniature EPSCs caused by presynaptic release of single quanta of glutamate or the amplitudes of EPSCs recorded in response to increasing presynaptic stimulus intensities.…”
Section: Discussionmentioning
confidence: 66%
See 3 more Smart Citations
“…Our previous studies of IM-AA mice showed that regulation of presynaptic Ca V 2.1 channels by CaS proteins contributes substantially to short-term synaptic plasticity in hippocampal synapses (21). In those studies, we found that the IM-AA mutation does not alter the frequency or amplitude of miniature EPSCs caused by presynaptic release of single quanta of glutamate or the amplitudes of EPSCs recorded in response to increasing presynaptic stimulus intensities.…”
Section: Discussionmentioning
confidence: 66%
“…In IM-AA synapses, the initial facilitation of EPSCs in response to a train of action potentials is reduced in amplitude, but facilitation eventually reaches a comparable level to WT and is sustained longer because the rapid phase of synaptic depression is slowed (21). Overall, the integral of EPSCs is actually increased during a train of stimuli (21). This persistent increase in EPSC amplitude during trains of stimuli in vivo may engage homeostatic regulatory mechanisms that weaken LTP, as we have reported here.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…4 A and B). A relevant question is activity-dependent Ca 2+ current facilitation because it modulates neurotransmission even with undistinguishable Ca 2+ influx under basal conditions (51). We thus applied 30 AP-like (AP-L) pulses (1 ms, +30 mV, 333 Hz) to mimic afferent AP activity (Fig.…”
Section: Resultsmentioning
confidence: 99%